Advances in Coalbed Methane Bioengineering: Mechanisms, Key Technologies, and Engineering Challenges - He, Haodong (International Journal of Natural Resources and Environmental Studies, 2026)
Coalbed methane (CBM) bioengineering has emerged as a promising approach for enhancing methane recovery from low-permeability and marginal coal reservoirs. This study systematically reviews the mechanisms of biogenic methane generation, recent advances in key bioengineering technologies, and the associated engineering challenges. Biogenic methane production in coal seams is driven by a multi-stage anaerobic metabolic network involving hydrolytic, fermentative, and methanogenic microorganisms, in which syntrophic interactions play a critical role in maintaining system stability and efficiency. Recent technological developments have focused on microbial stimulation and bioaugmentation strategies, aiming to enhance methane generation through nutrient regulation and functional microbial consortia. In addition, coupling biological processes with reservoir stimulation techniques, such as hydraulic fracturing and gas injection, has been explored to improve treatment efficiency and expand the effective reaction zone. Advances in monitoring and numerical simulation have further contributed to the understanding and optimization of subsurface biogeochemical processes. Despite these progress, field-scale application remains constrained by reservoir heterogeneity, slow microbial kinetics, and limited process controllability. Moreover, challenges related to microbial stability, substrate conversion efficiency, and environmental risks continue to hinder large-scale deployment. Overall, future research should focus on improving mechanistic understanding, enhancing process control, and integrating multidisciplinary approaches to advance CBM bioengineering toward practical and sustainable applications.